Problems and Strengths in Psychiatric Nursing in Poland: Current Legal Regulations and Results of Survey. (2nd April 2020) - Remberk, Barbara; Kosińska, Bożena; Brągoszewska, Joanna; Bogucka-Bonikowska, Anna; Twardowska, Monika
Abstract: Introduction: National health resources are considered inadequate to meet the needs of Mental Health services in Poland due in part to insufficient funding. The status of the nursing profession is autonomous and independent, and one that bears much public trust. Nevertheless, psychiatric nursing is in deep crisis. Aim of the study: To determine the strengths and limitations of the psychiatric nursing system in Poland. Method: Participants of a major Psychiatric Nursing Conference in Poland were surveyed in terms of professional job satisfaction and current problems encountered in psychiatric nursing. Results were appropriately categorized and subjected to quantitative analysis. Results: There were 74 subjects, amounting to a 70% response rate who completed the study questionnaire. Problem areas were focused on how the mental health system is organized and on staff working conditions that included terms of employment and salaries. The main reasons for job satisfaction were those issues associated with the treatment process. Two participants replied that they were not satisfied. Discussion: The numerous problems encountered in Polish psychiatry nursing require further debate and the updating of legal regulations to increase funding. Recently introduced regulations on the minimal standards acceptable for nurse/bed ratios have however been postponed until 2021. The issues concerning job satisfaction have also been referred to in previous studies. Implication for practice: The crisis facing psychiatric nursing in Poland requires systemic changes in both legal regulations and financing. Notwithstanding, such professionals and their societies could facilitate the necessary changes through enhancing public debate and stimulating nursing-focused research.